The complex association between the antioxidant defense system and clinical status in early psychosis. - Saínza García; Susana Alberich; Mónica Martínez-Cengotitabengoa; Celso Arango; Josefina Castro-Fornieles; Mara Parellada; Inmaculada Baeza; Carmen Moreno; Juan Antonio Micó; Esther Berrocoso; Montserrat Graell; Soraya Otero; et al. (PLoS ONE, 2018)
Oxidative stress is a pathophysiological mechanism potentially involved in psychiatric disorders. The objective of this study was to assess the relationship between total antioxidant status (TAS) and the functional status of patients with a first episode of psychosis at the onset of the disease. For this purpose, a sample of 70 patients aged between 9 and 17 years with a first episode of psychosis were followed up for a period of two years. Blood samples were drawn to measure TAS levels at three time points: at baseline, at one year, and at two years. Clinical symptoms and functioning were also assessed at the same time points using various scales. Linear regression analysis was performed to investigate the relationship between TAS and clinical status at each assessment, adjusting for potential confounding factors. The distribution of clinical variables was grouped in different percentiles to assess the dose-response in the relation between clinical variables and TAS. At baseline, patient's score on Children's Global Assessment Scale (CGAS) was directly and significantly associated with TAS with a monotonic increase in percentiles, and surprising this association was reversed after one and two years of follow-up with a monotonic decrease. In summary at the onset of the illness, TAS is positively related to clinical status, whereas as the illness progresses this correlation is reversed and becomes negative. This may be the result of an adaptive response.